Jamu Pada Pasien Tumor/Kanker sebagai Terapi Komplementer - Hasanah, Siti Nur; Widowati, Lucie (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2016)
To determine the use of herbs as complementary therapy in the practice of herbal medicine doctor , performed a cross sectional study , non-intervention in patients with doctors' complementary - alternative herbal medicine in hospitals , health centers, clinic of physician networks Indonesia. Using medical records and entry program on the website Badan Litbangkes, 10 months evaluated, analyzed descriptively using SPSS software version 19.0.Obtainable 72 patients tumor with 129 visits, varying between 1-4 each patient. The most commonly tumor found is breast (32%). Of the 71 patients with tumors, 80.3% receiving herbal, 14.1% received conventional and herbal, 2.8 % received conventional, herbal and traditional health , and 1.4 % received herbal and traditional health. Conventional included chemotherapy, analgesics/antiinflammatory, antibiotic, stomach medicine, tranexamat acids, vitamins, hormonal drugs. Vitamins most used, followed by analgesic/anti inflammatory. Herbal therapy (potion) most often given white turmeric and pearl grass. Herbs with the same components supplied by 8 different doctorspearl grass, white turmeric,bidara upas.There are 51,4% patients came with good quality of life, 40% moderate and 8.6% bad. After receiving 3 modality therapy, there are 79,6% patients with improved quality of life and 20,4% status quo.